Kapasitas Pemerintah Daerah Dalam Penyelenggaraan Perlindungan Anak Di Kabupaten Rokan Hilir Provinsi Riau - Khairul Rahman; Ranggi Ade Febrian; Mendra Wijaya (Management Studies and Entrepreneurship Journal (MSEJ), 2023)
The implementation of child protection in Rokan Hilir Regency is an important issue to study because there are still many cases of children related to physical and verbal violence, sexual violence, child custody, child neglect and children who are in conflict with the law. Violation of children's rights will actually hinder the nation's struggle, because children are the potential and the younger generation to continue the ideals of the nation's struggle. This study emphasizes that in the implementation of child protection, it is necessary to have the capacity of the local government. From the literature review conducted, there are several capacities needed for public organizations, namely the capacity of human resources, organization, systems and networks. This study uses qualitative methods with the main objective of being descriptive and revealing. The informant withdrawal technique used was purposive sampling using interview, observation and documentation data collection techniques. The results of the study found that there were still relatively high cases of children in Rokan Hilir Regency because the capacity of the local government of Rokan Hilir Regency had not been fulfilled in implementing child protection as seen from the dimensions of human resource capacity, financial capacity, organizational capacity, and network capacity.